Hospital hand hygiene monitoring: internal audits and the role of public health residents. (20th October 2021) - Moro, M; Vigezzi, GP; Chiappa, F; Salvati, S; Cocciolo, G; Oradini Alacreu, A; Capraro, M; Nizzero, P; Odone, A; Signorelli, C
Abstract: Background: Healthcare workers (HCW) adherence to hand hygiene (HH) is the most effective infection prevention and control (IPC) measure to fight healthcare-associated infections (HAI) and is a crucial component for standard precautions, especially in a pandemic context. As suggested by the WHO and Joint Commission Network Project, evaluating adherence to HH is essential to identify deficiencies and promote improvement interventions. Methods: San Raffaele Hospital in Milan, Italy, adopted internal audits to measure HCWs' adherence to HH according to WHO Guidelines. Public health (PH) residents were enrolled as auditors. They were trained with WHO technical manual for observers and handovers among residents. WHO observation form was used for collection. Process index was HH adherence, stratified by profession, unit, opportunity and indication. Results: 8 PH medical residents carried out observations from January 2018 to December 2019. 434 HCWs were observed in 26 hospital units (191 nurses, 148 physicians, 83 healthcare assistants and 11 other professionals). Global adherence was 53%, calculated on 1, 969 opportunities, and 2, 221 indications observed, followed by 932 hands rubbing and 110 handwashing. Most observations involved nurses (adherence of 53%) and physicians (54%). Global adherence was generally higher in medicine, specialist surgery and intensive-care units while lower in general surgery and rehabilitation units. Indications with the highest adherence were "after body fluid exposure risk" (69%) and "after touching a patient" (64%). The lowest adherence (44%) was observed for "before clean/aseptic procedure" indication. The belief that gloves use may replace HH might partially explain the data. Conclusions: Global HH adherence was in line with significant published data and was far better than 2016 data but slightly lower than observations in 2018 when the program started. We believe 2020 HH compliance could have changed due to HCW involvement in IPC against COVID-19. Key messages: Hand hygiene (HH) audits represent a crucial tool of clinical governance and risk management: auditors' training, monthly and annual reports, and feedbacks allowed to structure a virtuous process. If HH audits aim to improve practice we should understand when HH is most beneficial, assessing quality, improving performances through achievable targets using reproducible methods and technologies.